2016
DOI: 10.1177/1073191115601518
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Pre-Implant Psychosocial Factors and Spinal Cord Stimulation Outcome

Abstract: Spinal cord stimulation (SCS) has variable effectiveness in controlling chronic pain. Previous research has demonstrated that psychosocial factors are associated with diminished results of SCS. The objective of this investigation is to examine associations between pre-implant psychological functioning as measured by the Minnesota Multiphasic Personality Inventory-2-Restructured Form (MMPI-2-RF) and SCS outcomes. SCS candidates at two sites (total N = 319) completed the MMPI-2-RF and measures of pain, emotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 56 publications
4
33
0
Order By: Relevance
“…Sparkes et al demonstrated that autonomous coping and depression were shown to significantly correlate with improvements in VAS ( p < 0.001), ODI ( p = 0.011), anxiety ( p = 0.042), and depression ( p = 0.010) at 12 months . Block et al showed patients with aberrant negative thoughts, emotional internalizing disorder, and substance abuse were found to have a greater risk of not having their SCS expectations met or being dissatisfied with SCS . In contrast, Burchiel et al showed there was no direct correlation between outcome and psychological status in 34 patients at 3 months .…”
Section: Discussionmentioning
confidence: 99%
“…Sparkes et al demonstrated that autonomous coping and depression were shown to significantly correlate with improvements in VAS ( p < 0.001), ODI ( p = 0.011), anxiety ( p = 0.042), and depression ( p = 0.010) at 12 months . Block et al showed patients with aberrant negative thoughts, emotional internalizing disorder, and substance abuse were found to have a greater risk of not having their SCS expectations met or being dissatisfied with SCS . In contrast, Burchiel et al showed there was no direct correlation between outcome and psychological status in 34 patients at 3 months .…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in VAS by 50% at three months correlated with improved capacity for joy, as measured by DABS at a mean of five years follow‐up . In one study, pre‐operative sleep interference and pain self‐efficacy correlated with pain reduction of 50% or more, as measured by NRS . Significant preoperative measures that contributed to successful outcomes (defined as >50% pain reduction using NRS) include sleep interference using a 10‐point scale ( p = 0.026), depression using HADS ( p = 0.042), PCS ( p = 0.042), and PSEQ ( p = 0.0299) .…”
Section: Discussionmentioning
confidence: 99%
“…The reduced efficacy of SCS was attributed to technical factors that result in the loss of target area paresthesia and analgesic efficacy . However, recent studies suggest that the contribution of psychological factors also should be considered when investigating SCS efficacy . Chronic pain generally begins as a biological process, but psychological and social factors often play key roles in the development and experience of chronic pain.…”
Section: Discussionmentioning
confidence: 99%